Resource extractivism and alternatives : Latin American perspectives on development - Svampa, Maristella (2012)
Latin America presents a very polarised scenario. Currently, one of the most remarkable patterns is the passage from the Washington Consensus, based on financial valorization, to the Commodity Consensus, based on the large-scale extraction and exportation of natural goods. The article attempts to characterise the current situation and, at the same time, aims at a presentation of different political and intellectual tendencies: liberal neo-developmentalism, progressive neo-developmentalism and post-developmental thinking. The text analyses some links between these perspectives, especially between liberal neo-developmentalism and progressive neo-developmentalism, because both imply a return to the classical understanding of development in the strong sense, that is, associated with a productivist vision and incaccurate industrialist rhetoric. Finally and against his background, it presents some general lines of contemporary post-developmental thinking.
This article is based on the discussions during 2011 of the Permanent Working Group for Alternatives to Development (Grupo Permanente de Trabajo sobre Alternativas al Desarrollo 2011) supported by the Rosa Luxemburg Foundation. Within this framework an initial version of this text was presented for collective discussion in Quito and Brussels in June and July 2011 respectively. Furthermore, a later version was presented during the Latin American Seminar Derechos de la Naturaleza y Alternativas al extractivismo (Rights of Nature and Alternatives to the Extractive Economy) that we, as the Collective of Warning Voices (Colectivo Voces de Alerta 2011) jointly organised with CLAES, Jóvenes por la Igualdad (Youth for Equality) and CEPPAS in Buenos Aires in November 2011.
Keywords: Liberal neo-developmentalism; Progressive neo-developmentalism; Post-developmental thinking